Efficacy of acupoint stimulation as a treatment for uremic pruritus: A systematic review and meta-analysis - Lu, Ping-Hsun; Chung, Chia-Hsiang; Chuo, Hui-En; Lin, I-Hsin; Lu, Po-Hsuan (Frontiers in Medicine, 2022)
Background: Uremic pruritus causes sleep disturbances, poor quality of life, and increased mortality in patients with chronic kidney disease. Acupuncture has been shown to improve uremic pruritus. There is limited evidence of the efficacy of traditional Chinese therapies. We conducted a systematic review and meta-analysis to evaluate the efﬁcacy of acupoint stimulation therapy in patients with uremic pruritus. Methods: A systematic search of seven databases (up to June 2021) was conducted for randomized controlled trials that evaluated the clinical efficacy of acupuncture, acupressure, auricular acupressure, acupoint injection, acupoint thermal therapy, acupoint sticking therapy, or transcutaneous electrical acupoint stimulation in the treatment of patients with uremic pruritus. Two reviewers selected eligible articles for inclusion in the meta-analysis and evaluated the risk of bias via Cochrane Collaboration. The results of pruritus assessments and uremic pruritus-related laboratory parameters were analyzed. Results: Thirty-six trials published between 2002 and 2021, including a total of 2489 participants, were identified for inclusion in the meta-analysis. The effective rates for acupuncture, auricular acupressure, and the combination of acupoint injection and acupoint massage were significantly greater in patients with uremic pruritus compared to the control group. Conclusions: Acupuncture, auricular acupressure, and the combination of acupoint injection and acupoint massage seem to be effective in improving uremic pruritus in patients with chronic kidney disease. However, further investigation of these potential treatments is now warranted in larger patient populations and over a longer time frame.